RELATIONS BETWEEN MORPHOLOGICAL CHARACTERISTICS AND ACCURACY OF KICKING A BALL BY YOUNG FOOTBALL PLAYERS - Slobodan Andrašić; Darijan Ujsasi; Dejan Orlić; Milan Cvetković (Sport Mont, 2015)
Kicking a ball with foot or head are the basic elements of football, which can raise the efficiency of the game in terms of speed of action in terms of scoring goals. This is also the reason why the shot needs to be performed in a timely manner, usefully, and also quickly. The most commonly used kick in football is a inner-side instep kick, which is also the most accurate and the most used among the players (Cabri, De Prof, Dufour, & Clarys, 1998). Success in performing precise actions largely depends on the precision of locating targets in space, and therefore the role of our receptors is crucial for a successful precision (Szekeres, Santrač, Radosav, Toplak, Miljanić, 1994). The research problem was establishing the predictive impacts of morphological characteristics on the elevation accuracy of hitting the ball in young players. The subjects of the study were morphological characteristics and accuracy of the players. Aim of the paper was to determine the relation between morphological characteristics and precision of players aged 13-14 years from the Municipality of Loznica. Method: 50 players of the FK “Kabel” from Novi Sad, aged 13-14 years, were subjected to testing. Measurement of morphological characteristics was conducted. Specific (elevation) accuracy of hitting the ball towards the vertical and horizontal objective was also tested. By using the statistical analysis firstly the basic descriptive statistics of variables were determine. In order to determine the size of the impact of anthropometric characteristics on motor skills – precision, linear regression analysis was used. Results: Regression analysis showed that there was no statistically significant effect of the predictor system of morphological variables on the criterion variables tested: Precision of kicking the ball towards a horizontal target and Precision of kicking the ball towards a vertical target. The results pointed to the fact that some other characteristics and capabilities have greater influence on the manifestation of elevation precision of kicking the ball towards the horizontal and vertical target, in young players. Discussion: Research results indicated that there was no statistically significant effect of the predictor system composed of anthropometric characteristics on assessment of longitudinallity of skeleton and body volume regarding the test criteria.